Peranan Komite Nasional Kecelakaan Transportasi (KNKT) Dalam Penerbitan Laporan Akhir Kecelakaan Pesawat Sriwijaya SJ-182 Sebagai Upaya Tercapainya Kepastian Hukum Terhadap Keluarga Korban Kecelakaan Pesawat Sriwijaya SJ-182 - Amad Sudiro; Columbanus Priaardanto (Jurnal Kewarganegaraan, 2023)
Abstract The Sriwijaya SJ-182 plane crash has become an accident that adds to the record of aircraft accidents in Indonesia, the National Committee for Transportation Accidents (KNKT) is the institution in charge of the implementation of investigations into every plane crash in Indonesia, at the time of the Sriwijaya Air SJ-182 plane crash, KNKT also carried out an investigation into the accident, in every accident case handled, KNKT needs to issue a statement or final report as a summary and recommendations on the problems that caused the accident. But then of course for almost more than 2 (two) years KNKT has not provided the results of the report on the Sriwijaya Air SJ-182 aircraft accident case and only issued the final report in November 2022 , the problem in this paper is how the impact of legal certainty received by the victim's family on the issuance of the final knkt report on the sriwijaya sj-182 aircraft crash case, How is the role of KNKT in the process of issuing the final report on the Sriwijaya SJ-182 aircraft accident. This research is made based on normative juridical methods and is made based on primary and secondary legal materials. This accident was allegedly caused by an autothrottle (Auto Pilot) which had problems resulting in the crash of this aircraft. With the issuance of this final report, it is hoped that it can meet legal certainty for victims and it is hoped that in the course of every aircraft accident investigation process, KNKT can be more transparent and efficient in solving every aircraft accident case, as well as for the Indonesian government to pay more attention to the implementation of air transportation safety and is expected to provide upset prevention and recovery training (UPRT) training to every airline. Keyword: National Committee for Transportation Accidents (KNKT), Legal Certainty, Plane Crash.